Analisis Kebutuhan Bahan Ajar pada Tema 2 Selalu Berhemat Energi pada Kelas IV SD - Salsabila, Labibatus; Purnamasari, Iin; Patonah, Siti (CV. Supernova Office Stationary and Printing, 2023)
The type of research that will be used is R&D (Research and Development) development which refers to the Borg and Gall theory which consists of three main steps, namely preliminary studies, product design, and development and evaluation. This research will be conducted in February for the 2022/2023 academic year at SDN Godong 01, Godong District, Grobogan Regency, Central Java. The population in this study were fourth grade students at SDN Godong 01. In this study, a sample of product users was fourth grade students at SDN Godong 01, totaling 26 students. Based on the results of experiments by teachers and students that in interviews and questionnaires that have been obtained, it can be concluded that E-Book teaching materials are practical for use in learning and contain according to existing material and in accordance with the characteristics of students.